Implementasi Tekhnologi Dalam Membangun Ekonomi Masyarakat Desa Ketapang Lor: Digitalisasi Pemasaran Sebagai Solusi Problematika Marketing Kekinian - M. Afthon Al Ishaqi; Kholid Albar; Wiwik Saidatur Rolianah; Farhadi Arifiansyah; Nurul Istifadhoh (Institute for Research and Community Service (LPPM) of the Islamic University of Jember, 2025)
Digital transformation has changed the marketing landscape, offering new opportunities for rural areas to boost the local economy through marketing digitalization. This program aims to improve the digital literacy and marketing skills of the Ketapanglor Village community, focusing on the use of digital platforms to market local products. The program used a qualitative approach with descriptive methods, involving observation, in-depth interviews, and Focus Group Discussions (FGDs). Training and mentoring were provided to participants consisting of PKK mothers, MSME owners, and individuals interested in becoming affiliators. Results showed significant improvements in participants' digital literacy and marketing skills, which contributed to an average 30% increase in sales of local products. Key challenges faced include limited technological infrastructure and participant motivation. Ongoing support and collaboration with local stakeholders were identified as key factors to overcome these barriers. The program successfully improved the economic welfare of the Ketapanglor Village community and contributed to the development of the digital economy at the local level. The implications of the findings emphasize the importance of improving technological infrastructure and continued training to ensure the sustainability of the program. The program can serve as a model for other regions in implementing digital marketing strategies.